English | Español

Try our Free Online Math Solver!

Online Math Solver

 

 

 

 

 

 

 

 
 
 
 
 
 
 
 
 

 

 

 
 
 
 
 
 
 
 
 

Please use this form if you would like
to have this math solver on your website,
free of charge.


Factoring Quadratic Polynomials

In this handout we will factor quadratic polynomials of the form ax2 + bx + c , where a ,
b , and c are integers and a≠0 . Recall that factoring is actually the reverse process of multiplying ,
for example:

Example 1. (a) Multiply 3(3x + 1)(2x - 1) .
Solution : 3(3x + 1)(2x - 1) = 3(6x2 - 3x + 2x - 1) = 3(6x2 - x - 1) = 18x2 - 3x - 3 .
(b) Factor 18x2 - 3x - 3 .
Solution: 18x2 - 3x - 3 = 3(6x2 - x - 1) = 3(6x2 - 3x + 2x - 1) = 3(3x + 1)(2x - 1) .

Example 2. (a) Multiply (5x + 1)(5x - 1) .
Solution: (5x + 1)(5x - 1) = 25x2 - 5x + 5x - 1 = 25x2 - 1 .
(b) Factor 25x2 - 1 .
Solution: 25x2 - 1 = 25x2 - 5x + 5x - 1 = (5x + 1)(5x - 1) .
Notice that the last step in factoring was simply factoring by (re)grouping:

In Example 1: 6x2 - 3x + 2x - 1 = 3x(2x - 1) + 1(2x - 1) = (3x + 1)(2x - 1) ; and
in Example 2: 25x2 - 5x + 5x - 1 = 5x(5x - 1) + 1(5x - 1) = (5x + 1)(5x - 1) .

It remains to explain how to regroup or split the middle term bx ; in 1.b we replaced -x by
-3x + 2x , and in 2.b we replaced 0x by -5x + 5x . How do we determine those coefficients in
more complicated
cases? Let us consider the general case.

Suppose that it is possible to write the given polynomial ax 2 + bx + c as a product of the
form (mx + n)(px + q) where m , n , p , and q are integers to be determined. Then we have

(mx + n)(px + q) = mpx2 + mqx + npx + nq = mpx2 + (mq + np)x + nq = ax2 + bx + c ,
where mp = a , mq + np = b , nq = c . Written in reverse, this becomes an exercise in factoring;
the only problem is to replace b by the sum mq + np . We already know that the sum of mq
and np must be equal to b ; their product is (mq)(np) = (mp)(nq) = a × c . In other words, we
are looking for two integers whose sum is b and whose product is ac . The factoring method for
polynomials
of the form ax2 + bx + c can now be stated as follows:

(1) Calculate ac . Find two integers whose product is ac and whose sum is b .
(2) Replace the middle term, bx , by the sum of two terms whose coefficients are integers
found in (1).
(3) Factor by (re) grouping .

Notice that if ac ≠ 0 there are only finitely many ways to represent ac as a product of
two integers
, so that the method is guaranteed to produce a factoring or to show that no factoring
(over the integers) is possible. If ac = 0 just factor directly or use b = 0 + b .

Example 3. Factor 4x2 + 3x - 7 .

Solution: Here ac = 4(-7) = -28 , b = 3 , so we are looking for two numbers whose
product is -28 and whose sum is 3 . It is convenient to put the possible factors in a table:

First factor: 1 2 4 7 14 28
Second factor: -28 -14 -7 -4 -2 -1
Their sum: -27 -12 -3 3 12 27

The fourth column tells us to try 3x = 7x - 4x . We have 4x2 + 3x - 7 = 4x2 + 7x - 4x - 7
= x(4x + 7) - 1(4x + 7) = (4x + 7)(x - 1) .

Example 4. Factor 49x2 - 1 .
Solution: Here ac = 49(-1) = -49 , b = 0

First factor: -1 -7 . . .
Second factor: 49 7 . . .
Their sum: 48 0 . . .

The second column is the good one (the sum is zero as required ), so we omit the rest of the table.
This means 0x = -7x + 7x should work. We have 49x2 - 1 = 49x2 - 7x + 7x - 1 = 7x(7x - 1)
+ (7x - 1) = (7x - 1)(7x + 1) .

Example 5. Factor 4x2 - 4x + 1 .

Solution: Here ac = 4 × 1 = 4 , b = -4 . The (relevant part of the) table is now

First factor: -1 -2 . . .
Second factor: -4 -2 . . .
Their sum: -5 -4 . . .

Replacing -4x by -2x - 2x we have 4x2 - 4x + 1 = 4x2 - 2x - 2x + 1 = 2x(2x - 1) - (2x - 1)
= (2x - 1)(2x - 1) = (2x - 1)2 .

Example 6. Factor 5x2 + 7x + 3 .
Solution: Here ac = 5 × 3 = 15 , b = 7 . The table is

First factor: -1 -3 1 3
Second factor: -15 -5 15 5
Their sum: -16 -8 16 8

In this example the sum is never equal to 7 . Since we have tried every possible factoring of 15 ,
the conclusion is that 5x2 + 7x + 3 is not factorable over the integers.

Example 7. Factor 6x2 + 5xy + y2 .
Solution: Although this trinomial contains two variables , the same method still works.
Here we have ac = 6 × 1 = 6 , b = 5 and the table is

First factor: -1 -2 1 2
Second factor: -6 -3 6 3
Their sum: -7 -5 7 5

Using 5xy = 2xy + 3xy (from the last column) we have 6x2 + 5xy + y2 = 6x2 + 2xy + 3xy + y2
= 2x(3x + y) + y(3x + y) = (3x + y)(2x + y) .

Prev Next